Differences in systemic adaptive immunity contribute to the 'frequent exacerbator' COPD phenotype. Issue 1 (December 2016) - Geerdink, Jasper; Simons, Sami; Pike, Rebecca; Stauss, Hans; Heijdra, Yvonne; Hurst, John
Abstract Background Some COPD patients are more susceptible to exacerbations than others. Mechanisms underlying these differences in susceptibility are not well understood. We hypothesized that altered cell mediated immune responses may underlie a propensity to suffer from frequent exacerbations in COPD. Methods Peripheral blood mononuclear cells (PBMCs) were obtained from 24 stable COPD patients, eight frequent exacerbators (≥3 diary-card exacerbations/year) and 16 infrequent exacerbators (< 3 diary-card exacerbations/year). Detailed multi-parameter flow cytometry was used to study differences in innate and adaptive systemic immune function between frequent and infrequently exacerbating COPD patients. Results The 24 COPD patients had a mean (SD) age of 76.3 (9.4) years and FEV1 1.43 (0.60)L, 53.3 (18.3)% predicted. PBMCs of frequent exacerbators (FE) contained lower frequencies of CD4+ T central memory cells (CD4+ Tcm) compared to infrequent exacerbators (IE) (FE = 18.7 %; IE = 23.9 %;p  = 0.035). This observation was also apparent in absolute numbers of CD4+ Tcm cells (FE = 0.17 × 10^6/mL; IE = 0.25 × 10^6/mL;p  = 0.035). PBMCs of FE contained a lower frequency of CD8+ T effector memory cells expressing HLA-DR (Human Leukocyte Antigen - D Related) compared to IE COPD patients (FE = 22.7 %; IE = 31.5 %;p  = 0.007). Conclusion Differences in the adaptive systemic immune system might associate with exacerbation susceptibility in the 'frequent exacerbator' COPD phenotype. These differences include fewer CD4+ T central memory cells and CD8+ T effector memory cells. Trial registration Not applicable.